Penerapan Metode CIBMO (Circle Ball Movement) dalam Pembelajaran PJOK untuk Meningkatkan Motivasi Belajar, Kerja Sama, dan Kesetaraan Gender Siswa Sekolah Dasar - Suryana, Yana; Sobarna, Akhmad; Budiman, Ali (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of the CIBMO (Circle Ball Movement) Method in Physical Education, Sports, and Health (PJOK) learning on learning motivation, cooperation, and gender equality of elementary school students. The study used a quantitative approach with a quasi-experimental design involving 32 fourth-grade students of Nagrak Public Elementary School, Cianjur. Data collection was carried out through questionnaires and observation sheets before and after the implementation of the CIBMO Method in one learning meeting. Data were analyzed using descriptive statistics and paired sample t-tests. The results showed an increase in the average value of students' learning motivation, cooperation, and gender equality, and the results of the hypothesis test showed a significance value <0.05, indicating a significant effect. The conclusion of this study shows that the CIBMO Method is effective as an alternative PJOK learning model that is able to increase learning motivation, strengthen cooperation, and encourage gender equality of elementary school students. Keywords: Cooperation, Gender Equality, CIBMO Method, Learning Motivation, Physical Education.